Pelaksanaan Layanan Bimbingan Kelompok Dalam Meningkatkan Komunikasi Teman Sebaya Di Mas Pab Sampali - Mona Safitri, Nurlia (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This type of research in this paper is a descriptive qualitative research field. The informants in this study are divided into two, namely key informants and informants and key data collection techniques using data collection tools namely observation interview documentation while data analysis of the results of this study is based on analysis. Consists of three analytical flows that interact, namely data reduction, data presentation, and drawing conclusions. The purpose of this study 1) to find out the implementation of guidance service for MAS PAB Sampali. 2) to find out peer communication before group guidance is done at the MAS PAB Sampali. 3) to know the communication of peers after the group guidance is done at the MAS PAB Sampali. From the result of the study namely the implementation of guidance and counseling services include the provision of group guidance services in the from of communication at school are implemented both programmed and in accordance with student needs. In accordance with the purpose of group guidance services namely to be able to add insight to understanding to know certain ways or habits through learning activities.